Route to benzimidazol-2-ones via decarbonylative ring contraction of quinoxalinediones: application to the synthesis of flibanserin, A drug for treating hypoactive sexual desire disorder in women and marine natural product hunanamycin analogue - Shingare, Rahul D.; Kulkarni, Akshay S.; Sutar, Revannath L.; Reddy, D. Srinivasa (ACS Omega, 2017)
A simple and practical method to access a variety of benzimidazol-2-ones is reported here. A series of N-alkylsubstituted benzimidazol-2-ones were synthesized by decarbonylative ring contraction starting from corresponding quinoxalinediones for the first time. The utility of the method has been demonstrated by synthesizing recently approved controversial drug flibanserin (Addyi) and a urea analogue of marine antibiotic natural product hunanamycin-A.